Vitamin D status in peripheral vascular diseases: A longitudinal prospective study - Prem Singh; Sanjay Kumar; Koushik Biswas; Abha Jyoti; Amarendra Tripathi (Asian Journal of Medical Sciences, 2022)
Background: Peripheral artery disease (PAD) is due to abnormal Narrowing of arteries other than heart and brain (primarily due to atherosclerosis). PAD is the most common form of PVD. Aims and Objectives: In the present study, we analyzed Vitamin D association with peripheral vascular diseases as well as coagulation and inflammation parameters. Materials and Methods: The study was conducted for 100 PAD patients of 18–70 years age and divided in Group I≤20ng/ml and Group II>20ng/ml for serum Vitamin D level. A single, oral, and high- dose Vitamin D3 supplementation 1,20,000IU was given in GroupI. At baseline and at the end of the study after 1 month, Ankle Brachial Index, modified Rankin Scale, Vitamin D, Inflammation and coagulation parameter, HbA1c, etc., were performed in all patients. Evaluation was done using SPSS. The level P<0.05 was considered as the cut off value of significance. Results: The majority of the PAD patients were Vitamin D deficient and have higher HbA1c level with statistically significant (P<0.05) association. This is because low Vitamin D is the risk factor for diabetes in which HbA1c level is higher. Conclusion: Asingle, oral, and high-dose Vitamin D3 supplementation did not alter parameters of inflammation and hemostasis in patients with peripheral arterial disease, adding more data to other studies that did not confirm a causal role of Vitamin D in cardiovascular disease.